Socioeconomic profile of the actors involved in the production and commercialization of the zoohandicraft in Recife, Pernambuco – Brazil - Alves, Marcos Souto; Silva, Maria Aparecida da; Pinto, Stefane de Lyra (Revista Nordestina de Zoologia, 2010)
In Pernambuco’s coast the handicraft production using animals as raw material exhibit the biodiversity and richness littoral ecosystem of the Northeast region. The aim of this work was to know the socioeconomic profile of the producers, traders and final consumers of the zoohandicrafty in the Recife city as well as yours respective knowledge grades on the ecological questions that involve this economic activity. Data were obtained through interviews with of the workmanships, traders and buyers of the zoohandicrafty using questionnaires previously developed in the main handicraft commerce points. The zoohandicraft production engages several members of the family and represented the only or main economic source, with strong familiar hereditary tradition. On the perception of the people interviewed about zoohandicraft and ecology is related only to the fact that objects show Northeast littoral natural beauties. This work suggests that the public organ should offer other alternatives for handicraft productions that take no risk to the Northeast marine macrofauna.